Responses of Islamic banking variables to monetary policy shocks in Indonesia - Aula Ahmad Hafidh (Islamic Economic Studies (IES), 2021)
Purpose This paper investigates the structural model of vector autoregression (SVAR) of the interdependent relationship of inflation, monetary policy and Islamic banking variables (RDEP, RFIN, DEP, FIN) in Indonesia. By using monthly data for the period 2001M01-2019M12, the impulse response function (IRF), forecasting error decomposition variation (FEDV) is used to track the impact of Sharī'ah variables on inflation (prices). Design/methodology/approach This research uses quantitative approach with SVAR model to reveal the problem. Findings The empirical results of SVAR, the IRF show that policy shocks have a negative impact on all variables in Islamic banking except the equivalent deposit interest rate (RDEP). The impact of both conventional (7DRR) and Sharī'ah (SBIS) policies has a similar pattern. While the transmission of Sharī'ah monetary variables as a policy operational target in influencing inflation is positive. In addition, the FEDV clearly revealed that the variation in the Sharī'ah financial sector was relatively large in monetary policy shocks and their role in influencing prices. Originality/value The empirical results of SVAR, the IRF show that policy shocks have a negative impact on all variables in Islamic banking except the equivalent deposit interest rate 'RDEP'. The impact of both conventional "7DRR" and Sharī'ah "SBIS" policies has a similar pattern. While the transmission of Sharī'ah monetary variables as a policy operational target in influencing inflation is positive. In addition, the FEDV clearly revealed that the variation in the Sharī'ah financial sector was relatively large in monetary policy shocks and their role in influencing prices.
Keywords: C32; E44; E58; 330; Islamic banking; Monetary policy transmission mechanism; Structural VAR